2020
DOI: 10.1007/s11056-020-09803-4
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal timing and recurrence of methyl jasmonate treatment influence pine weevil damage to Norway spruce seedlings

Abstract: Defense can be induced in conifer seedlings to reduce pine weevil (Hylobius abietis) damage, by treatment with the plant hormone methyl jasmonate (MJ). Few studies have addressed important practical issues regarding the use of MJ such as treatment incidence and timing, seedling age and its compatibility with plant nursery practices. We examined if levels of pine weevil damage depend on seasonal timing and recurrence of MJ treatment, and if the observed effects depend on plant age. Norway spruce (Picea abies) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 49 publications
5
20
0
Order By: Relevance
“…Our results are in line with previous studies on MeJA-induced resistance in P. abies and other conifers species. Decreases in pine weevil damage ranging from 50 to 70%, for example, have been shown to occur after consecutive treatment with 10 mM MeJA in Norway spruce seedlings ( Chen Y. et al, 2020 ). For other species such as Pinus pinaster , pine weevil damage was reduced by 80% after treatment with 100 mM MeJA ( Moreira et al, 2009 ), and reduced by 30–60% for P. pinaster , P. radiata , P. sylvestris , and P. abies seedlings treated with 25 mM MeJA ( Zas et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our results are in line with previous studies on MeJA-induced resistance in P. abies and other conifers species. Decreases in pine weevil damage ranging from 50 to 70%, for example, have been shown to occur after consecutive treatment with 10 mM MeJA in Norway spruce seedlings ( Chen Y. et al, 2020 ). For other species such as Pinus pinaster , pine weevil damage was reduced by 80% after treatment with 100 mM MeJA ( Moreira et al, 2009 ), and reduced by 30–60% for P. pinaster , P. radiata , P. sylvestris , and P. abies seedlings treated with 25 mM MeJA ( Zas et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Protection against pine weevil damage is necessary for only a few years after planting, since pine weevils cause high mortality only at the seedling stage. In terms of applicability, several studies have shown that treating seedlings with MeJA can be compatible with nursery practices ( Fedderwitz et al, 2019 ; Chen Y. et al, 2020 ). Infection by E. polonica occurs when mature trees are attacked by the spruce bark beetle, and it would be important for these trees to be constitutively more resistant to infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of MeJA treatment on pine weevil damage has been shown to be dose dependent (Moreira et al, 2009;Zas et al, 2014). In one of our previous experiments, a higher dose of MeJA (three consecutive sprayings of 10 mM MeJA) resulted in greater Norway spruce resistance to pine weevil damage relative to plants receiving a lower dose (one spraying of 10 mM MeJA) (Chen et al, 2020). The low dose of MeJA in our previous study on Norway spruce was the same as the low dose used in this study on Scots pine seedlings, and the amount of debarked area received by these two conifer species were similar in both studies.…”
Section: Source Of Variancementioning
confidence: 91%